Biomechanical and physiological effects of a passive upper-body exoskeleton during stair ascent and descent - Gabriela Garcia; Milena Espoz; Camilo Albuja; Rafaella Yañez; Paul G. Arauz; Bernard J. Martin (PLoS ONE, 2026)
The market has seen the emergence of various passive exoskeletons designed to assist with carrying tasks; however, evidence of their effects during stair negotiation remains limited. In this study fifteen female and fifteen male participants carried a 12-kg load with and without an upper-body passive exoskeleton (CarrySuit Ⓡ ) while ascending and descending stairs. The impact of the CarrySuit Ⓡ was evaluated through measurements of heart rate, muscle activity, and joint range of motion during both stair ascent and descent. The results indicated that heart rate and muscle activity in the biceps brachii and erector spinae were reduced during both ascent and descent when wearing the exoskeleton, except in females during descent, where muscle activity remained comparable between conditions. An increase in upper-leg muscle activity was observed only in males during ascent, while lower-leg muscle activity was reduced during descent for all participants. Some side-based asymmetries in lower-limb activation were observed, but they were generally modest when using the exoskeleton. Use of the CarrySuit Ⓡ was associated with reduced joint range of motion, particularly in males, affecting the shoulders, elbows, pelvis, hips, and thorax. In females, reductions in range of motion were limited to the neck and thorax. In contrast, increases in range of motion were observed in the ankles, knees, hips, and shoulders in females, and in the ankles and knees in males. Lower perceived discomfort was reported by all participants when using the exoskeleton, with broader relief observed among male users. These findings suggest that the CarrySuit Ⓡ has a positive impact on physiological, biomechanical, and perceptual outcomes during stair-based load carrying, and may serve as a viable ergonomic solution for work environments where mechanical aids are impractical.